Non-magnetic 30 dB integrated optical isolator in III/V material - Ibrahim, SK; Bhandare, S; Sandel, D; Zhang, H; Noé, Reinhold (ELECTRONICS LETTERS)

Void growth in finite deformation elasto-plasticity due to hydrostatic stress states - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)

Stress mode dependent weighting functions for simulation of asymmetric creep effects - Mahnken, Rolf (PAMM)

Positivity of Dunkl's intertwining operator via the trigonometric setting - Rösler, Margit; Voit, Michael (International Mathematics Research Notices)
In this note, a new proof for the positivity of Dunkl's intertwining operator in the crystallographic case is given. It is based on an asymptotic relationship between the Opdam-Cherednik kernel and the Dunkl kernel as recently observed by M. de Jeu, and on positivity results of S. Sahi for the Heckman-Opdam polynomials and their non-symmetric counterparts.

Die ‚story‘ der unterdrückten Komponistin – ein feministischer Mythos? Anmerkungen zu einigen neuen Publikationen über Fanny Hensel - Grotjahn, Rebecca (Frankfurter Zeitschrift für Musikwissenschaft)

Tax neutrality under irreversibility and risk aversion - Niemann, Rainer; Sureth-Sloane, Caren (Economics Letters)

Learning to Manipulate Objects: A Quantitative Evaluation of Motionese - Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta (Third International Conference on Development and Learning (ICDL 2004))
One dream of robotics research is to build robot companions that can interact outside the lab in real world environments such as private homes. There has been good progress on many components needed for such a robot companion, but only few systems are documented in the literature that actually integrate a larger number of components leading to a more natural and human-like interaction with such a robot. However, only the integration of many components on the same robot allows us to study embodied interaction and leads to new insights on how to improve the overall appearance of such a robot companion. Towards this end, we present the Bielefeld Robot Companion BIRON as an integration platform for studying embodied interaction. Reporting different stages of the alternating development and evaluation process, we argue that an integrated and actually running system is necessary to assess human needs and demands under real life conditions and to determine what functions are still missing. This interplay between evaluation and development stimulates the development process as well as the design of appropriate evaluation metrics. Moreover, such constant evaluations of the system help identify problematic aspects that need to be solved before sophisticated robot companions can be successfully evaluated in long-term user studies.

Polarized electroluminescence of a discotic mesogenic compound - Benning, Stephan A.; Oesterhaus, Reinhold; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

‚An der Spitze der musikalischen Bewegung‘ – Die Reisen der Bilse’schen Kapelle - Grotjahn, Rebecca (Mitteilungen der Benjamin Bilse Gesellschaft)

Koketterie und Wahnsinn – zur Weiblichkeit des Koloraturgesangs - Grotjahn, Rebecca (Oper aktuell. Bd. XXVII: Die Bayerische Staatsoper 2004/05. Anlässlich der Münchner Opern-Festspiele 2004)